Diagnostics and Therapy for Malignant (Degenerate) Colon Endometriosis – Three Case Reports - Schutz, R.; Woziwodzki, J.; Schweppe, K.-W. (Geburtshilfe und Frauenheilkunde, 2016)
Malignant degeneration of colon endometriosis is a very rare event. We report here on three cases. A 48-year-old woman with a 10-year history of endometriosis was treated for a rectal adenocarcinoma, a 61-year-old G1P1, who was operated at the age of 40 years for ovarian endometriosis and again at the age of 53 years for an endometriosis-associated endometroid ovarian carcinoma, presented for therapy for a lymph node recurrence of the ovarian cancer and, secondly, due to a malignantly degenerated rectum-sigmoid colon endometriosis; furthermore a 54-year old woman with a 21-year history of endometriosis was operated for malignant colon endometriosis. The tumour occurred during an adjuvant anti-oestrogen treatment with an aromatase inhibitor following surgical and radiotherapy for breast cancer. In all cases a radical cancer operation was followed by adjuvant chemotherapy and in one case with an additional radiotherapy. In the follow-up periods of 18 months, 2 and 5 years, respectively, all women remained free of recurrences. Although this is not a randomised controlled study due to the rare occurrence of such cases, a radical operation followed by individualised adjuvant therapy appears to be the treatment of choice.
Keywords: bowel endometriosis; malignant degeneration; endometriosis-associated carcinoma